EVALUATION OF PROFITABILITY RATIOS PERFORMANCE AND ITS IMPACT ON STOCK PRICE OF PT. UNILEVER INDONESIA TBK - Haryati, Sani (Universitas Tanjungpura, 2025)
This study aims to evaluate the financial performance of PT Unilever Indonesia Tbk. based on profitability ratios, namely Return on Assets (ROA) and Return on Equity (ROE), and their impact on the company's stock price. The data used include quarterly financial reports and stock prices of PT Unilever Indonesia Tbk. from the first quarter of 2020 to the third quarter of 2024. The research method employs multiple regression analysis with hypothesis testing conducted through t-tests (partial) and F-tests (simultaneous). The results indicate that, partially, ROA has a significant effect on stock price, with a significance value of 0.019 ( 0.05) and a t-value of 2.606 exceeding the t table value of 2.131. Conversely, ROE does not significantly affect stock price, as evidenced by a significance value of 1.563 ( 0.05) and a t-value of 0.634, below the t table threshold. Simultaneously, ROA and ROE significantly influence stock price, with an F-value of 4.403 exceeding the F Table value of 3.68 and a significance value of 0.030 ( 0.05). The contribution of ROA and ROE to stock price variation is reflected in an R2 value of 0.355, indicating that 35.5% of stock price changes are explained by these variables, while the remaining 64.5% are influenced by factors outside the study. These findings recommend that the company continues to enhance asset utilization to optimize ROA, which has proven significant in affecting stock price. Additionally, future researchers are advised to consider other variables, such as capital structure, dividend policies, and market conditions, to provide a more comprehensive understanding of the factors influencing stock price.